Ca–La layered double hydroxide (LDH) for selective and efficient removal of phosphate from wastewater. (June 2023) - Cao, Yuhang; Wu, Xuewei; Li, Biqing; Tang, Xia; Lin, Xueran; Li, Pengfei; Chen, Hang; Huang, Fu; Wei, Chaohai; Wei, Jian; Qiu, Guanglei
Abstract: Adsorption showed advantages in removing phosphorus (P) at low concentrations. Desirable adsorbents should have sufficiently high adsorption capacity and selectivity. In this study, a Ca–La layered double hydroxide (LDH) was synthesized for the first time by using a simple hydrothermal coprecipitation method for phosphate removal from wastewater. A maximum adsorption capacity of 194.04 mgP/g was achieved, ranking on the top of known LDHs. Adsorption kinetic experiments showed that 0.02 g/L Ca–La LDH could effectively reduce PO4 3– P from 1.0 to <0.02 mg/L within 30 min. With the copresence of bicarbonate and sulfate at concentrations 17.1 and 35.7 times of that of PO4 3– P, the Ca–La LDH showed promising selectivity towards phosphate (with a reduction in the adsorption capacity of <13.6%). In addition, four other (Mg–La, Co–La, Ni–La, and Cu–La) LDHs containing different divalent metal ions were synthesized by using the same coprecipitation method. Results showed much higher P adsorption performance of the Ca–La LDH than those LDHs. Field Emission Electron Microscopy (FE-SEM)-Energy Dispersive Spectroscopy (EDS), X-ray Diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Fourier Transform Infrared Spectroscopy (FTIR), and mesoporous analysis were performed to characterize and compare the adsorption mechanisms of different LDHs. The high adsorption capacity and selectivity of the Ca–La LDH were mainly explained by selective chemical adsorption, ion exchange, and inner sphere complexation. Graphical abstract: Image 1 Highlights: Ca–La layered double hydroxide was synthesized for the first time. The maximum P adsorption capacity was 194.04 mg/g. Selective P adsorption was achieved at high bicarbonate and sulfate concentrations. Efficient reducing the PO4 3– P concentration to <0.02 mg/L within 30 min.